Predictive value of GRACE and APACHE-II scores on mortality in acute coronary syndrome patients admitted to CVCU - Prasetya, Indra; Hakim, Dennis Ievan; Anjarwani, Setyasih (Universitas Brawijaya, 2025)
BACKGROUND: Acute coronary syndrome (ACS) is correlated with elevated death and fatality rates. The Global Registry of Acute Coronary Events (GRACE) score is frequently employed for risk stratification in ACS. Nevertheless, intensive care physicians frequently utilize more comprehensive and general prognostic judgments derived from critically ill individuals, one of which is the Acute Physiology and Chronic Health Evaluation II (APACHE-II) score. OBJECTIVES: To compare the effectiveness of the score compared to APACHE-II score in predicting cardiovascular care unit () mortality. METHODS: A Retrospective cohort study was carried out at a single center, utilizing data from ACS patients admitted to the CVCU of RSUD Dr. Saiful Anwar Malang from 2021 to 2023. Both GRACE and APACHE-II scores were computed at the initial admission to hospital. The discriminative capability was computed using the area under the curve (AUC), and calibration was verified by the Hosmer-Lemeshow (HL) test. Multivariate logistic regression was performed to ascertain independent determinants of death. RESULTS: CONCLUSION: APACHE-II exhibited enhanced efficacy in predicting CVCU mortality in ACS patients, and both scoring systems continue to serve as valuable instruments.